Structural and Metamorphic History of the Leech River Shear Zone, Vancouver Island, British Columbia. Issue 11 (7th November 2022) - Seyler, C. E.; Kirkpatrick, J. D.; Faber, C.; Licht, A.; Šilerová, D.; Regalla, C.
Abstract: The Leech River Shear Zone (LRSZ) on southern Vancouver Island separates the metasedimentary schists of the Leech River Complex (LRC) from the accreted oceanic plateau of the Siletz‐Crescent terrane. The juxtaposition of these rock units suggests a possible origin as a subduction plate boundary but tectonic context of the LRSZ has yet to be fully established. We present field, microstructural, petrological, and geochronological observations that constrain the structural and metamorphic history of LRSZ. The mylonite zone of the LRSZ straddles the lithologic contact between the schists of the LRC and basalts of the Siletz‐Crescent terrane. Foliation orientations, a steeply plunging stretching lineation, and kinematic indicators all suggest reverse‐sinistral motion. Compositions of garnet in the schist and amphibole in the metabasalt record synkinematic growth at temperature and pressure conditions of 550°C–570°C and 450–490 MPa. These metamorphic conditions require elevated geotherms that are consistent with plate models that position the Kula‐Farallon Ridge and Yellowstone Hotspot in the region in the Eocene (∼50 Ma). Detrital zircon U‐Pb age distributions for the Leech River Schist have Paleocene maximum depositional ages and are similar to the Upper Nanaimo Group that unconformably overlies the Wrangellia terrane. Our ages support early Paleocene deposition of the schist in a subduction trench/slope environment followed by underthrusting and underplating. These results establish the exhumed mylonite zone of the LRSZ as a paleo‐plate interface that was active during Eocene subduction. Key Points: Leech River Shear Zone confirmed as a hot, Eocene‐age paleo‐subduction interface High‐temperature metamorphism produced by ridge subduction during accretion of Siletz‐Crescent terrane New detrital zircon ages from the Leech River Schist support near‐trench deposition during Paleocene